Bridging the Access Gap: The Telepractice Experience of Speech Therapists and Audiologists at a Public Health Care Facility in South Africa - Shelissa Govender; Annika L. Vallabhjee; Chenay R. Charles; Darike Roesch; Sadna Balton (International Journal of Telerehabilitation)
South Africa is a low to middle income country (LMIC) with a population of 60 million people. The public health sector serves more than 80% of the population. Chris Hani Baragwanath Academic Hospital is a central level public health care facility situated in Gauteng. The Speech Therapy and Audiology Department provides insight into their telepractice services through a qualitative approach. The onset of the COVID-19 pandemic resulted in therapists exploring telepractice as a sustainable model of service delivery. Therapists and patients encountered many challenges to the implementation of telepractice, however, the commitment of therapists ensured that creative solutions were developed. A comprehensive needs analysis at public health institutions is required to ensure the sustainability of telepractice. A hybrid model (telepractice and in-person consults) holds the potential to reduce the financial burden on patients and increase access to quality patient- centered care.